Co-Creation for Sustainability : The un SDGs and the Power of Local Partnerships. - Ansell, Christopher. (Emerald Publishing Limited, 2022)
The ebook edition of this title is Open Access and freely available to read online.Co-Creation for Sustainabilitybrings global SDGs to the local level, explaining local co-creation practices, the creation of collaborative platforms, and the empowerment of stakeholders to have a positive collective impact.